Determination of 5-Hydroxymethylfurfural and Saccharides in Mead - Juričová, Miroslava; Řezková, Soňa; Moravcová, Kamila; Fischer, Jan; Česlová, Lenka (Výzkumný ústav pivovarský a sladařský, a.s., 2018)
This work is focused on determination of 5-hydroxymethylfurfural (HMF), glucose, fructose and sucrose in meads. Reversed-phase high performance liquid chromatography with spectrophotometric detection was used for the separation of HMF. Saccharides were separated using hydrophilic interaction liquid chromatography with refractive index detector. These techniques were employed for determination of the content of HMF and saccharides in 23 samples of meads obtained from different producers. The content of these compounds is strongly dependent on the technological process of mead production and could be used as a marker of mead quality. The content of HMF is lower in samples obtained from beekeepers than in samples purchased in local stores.
Stanovení 5-hydroxymethylfurfuralu a vybraných sacharidů v medovinách
Keywords: Saccharides; 5-hydroxymethylfurfural; mead; liquid chromatography; sacharidy; 5-hydroxymethylfurfural; medovina; kapalinová chromatografie